Synthesis of a low-firing BaSi2O5 microwave dielectric ceramics with low dielectric constant. Issue 12 (15th June 2022) - Wu, Pei; Yang, Hongyu; Yang, Hongcheng; Gui, Ling; Wang, Yuchen; Liu, Qian; Li, Enzhu
Abstract: In this study, BaSi2 O5 ceramics with an orthorhombic structure were synthesized by using a traditional solid-state method at a low temperature by doping with Li2 O–B2 O3 –CaO–CuO (LBCC) glass. The phase composition, mechanism of low-temperature sintering, microwave dielectric properties, and changes in the mesophase during the heating of low-temperature sintered BaSi2 O5 ceramics were examined by performing an X-ray diffraction analysis. A compact matrix of BaSi2 O5 can be wetted by the liquid phase of the formed LBCC glass. Therefore, LBCC glass with different doping percentages can effectively reduce the sintering temperature of BaSi2 O5 . The microwave dielectric properties of BaSi2 O5 ceramics sintered at 900 °C at 4 wt% of LBCC glass were determined: εr = 7.32, Q × f = 19, 002 GHz, and τ f = −35.8 ppm/°C. The chemical compatibility of the samples with Ag was studied at 4 wt% doping with LBCC glass, and the samples were fired for 4 h at 900 °C.